Distribution of Dtpa-extractable Fe, Mn, Zn and Cu in Teak and Sandalwood-Supporting Soils in Seoni District, Madhya Pradesh - Choudhari, Pushpajeet L.; Prasad, Jagdish; Gurav, Priya P. (Indian Forester, 2018)
Two pedon from teak and two from sandalwood-supporting soils occurring on different landforms were studied for their morphology, DTPA-extractable micronutrient cations and some relevant physico-chemical soil properties in Seoni district, Madhya Pradesh. Teak-supporting Parasia pedon (plateau) was characterised by shallow, dark reddish brown soils with argillic clay horizon (Clayey Typic Haplustalf) whereas Mohgaon (undulating basaltic plateau) pedon had very deep solum, dark reddish brown, clayey soil with more than 50 per cent gravels (Clayey-skeletal Typic Rhodustalf). The sandalwood (natural)-supporting Salaia pedon (foot slope) was characterised by shallow, dark reddish brown to reddish brown soils classified as Clayey Typic Haplustept whereas other pedon (scarp slope) was shallow, very dark greyish brown, Clayey Typic Haplustept. The pH of the soils varied from 5.9 to 6.7 in teak-growing soils but it was 6.8 to 7.0 in sandalwood-growing soils. The organic carbon varied from 1.26 to 2.37 % in teak-growing soils which was higher than the sandalwood-growing soils and it ranged from 0.37 to 1.56 %. Cation exchange capacity ranged from 8.53 to 31.31 cmol(p+)kg-1 and 34.27 to 39.70 cmol(p+)kg-1 in teak and sandalwood-growing soils respectively. The soils had DTPA-Fe (1.68 to 36.04 mg kg-1),Mn (13.64 to 136.7 mg kg-1), Zn (0.60 to 2.60 mg kg-1) and Cu -1 (1.38 to 20.38 mg kg-1) in teak supporting soils. In sandalwood-supporting soils DTPA-Fe ranged from 6.68 to 14.94 mg kg-1, Mn (53.82 to 78.52 mg kg-1), Zn (0.48 to 1.40 mg kg-1)and Cu (7.60 to 10.98 mg kg-1). In general, pH showed negative correlation with micronutrient cations while, clay content and OC had positive correlation with DTPA-Fe, Mn, Zn and Cu. Surface layer of the soil had higher concentration of DTPA-extractable cations.